2017
DOI: 10.1136/annrheumdis-2017-211375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of 5-year drug-free remission-steered treatment in patients with early arthritis: IMPROVED study

Abstract: Five years of DFR-steered treatment in patients with early RA resulted in almost normal functional ability without clinically relevant joint damage across treatment groups. Patients who achieved early remission had the best clinical outcomes. There were no differences between the randomisation arms. SDFR is a realistic treatment goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 34 publications
3
49
1
2
Order By: Relevance
“…In this regard, we have demonstrated that the maintenance of remission is possible in RA, especially in patients with RA who had received early treatment and in whom disease activity was well controlled before discontinuation of adalimumab (ADA), an anti-TNF agent [7,8]. However, little has been reported on the long-term outcome of biologics-free remission [9][10][11][12][13]. Since RA is a chronic disease, it is also important clinically to determine the long-term consequences of discontinuation of biologics.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have demonstrated that the maintenance of remission is possible in RA, especially in patients with RA who had received early treatment and in whom disease activity was well controlled before discontinuation of adalimumab (ADA), an anti-TNF agent [7,8]. However, little has been reported on the long-term outcome of biologics-free remission [9][10][11][12][13]. Since RA is a chronic disease, it is also important clinically to determine the long-term consequences of discontinuation of biologics.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are several cohort studies reporting the rates of SR from 3% to 53%, mainly due to the different definitions of SR . Although some of them further explored the relevant prognostic factors, obvious inconsistencies exist in the effect of gender, serological antibodies, baseline disease activity, and initial treatment regimens .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Sustained remission (SR), rather than remission at a single time point, is more desirable due to its association with better RA prognosis, 5,6 reflected by quality of life, physical function, as well as radiographic progression. [7][8][9] To date, there are several cohort studies reporting the rates of SR from 3% to 53%, mainly due to the different definitions of SR. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Although some of them further explored the relevant prognostic factors, [13][14][15][16]18,19,[21][22][23][24] obvious inconsistencies exist in the effect of gender, 13,16,19 serological antibodies, 13,16,24 baseline disease activity, 13,19,21 and initial treatment regimens. 18 Moreover, participants in nearly all previous reports were exclusively diag...…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Boolean remission remains hard to achieve, being observed in less than 20% of the patients in this study and in similar early arthritis cohorts (9). Such a low proportion does not seem to be significantly increased by the adoption of more aggressive strategies, such as earlier treatment initiation within the phase of undifferentiated arthritis and early combination with biological DMARDs, as in the IMPROVED study (32), or treatment to the target of imaging remission, such as in the ARCTIC trial (33).…”
Section: Discussionmentioning
confidence: 99%